Pengaruh Beban Pajak Tangguhan, Motivasi Kontrak Utang, dan Risiko Litigasi Terhadap Manajemen Laba - Fitria, Wika; Cerya, Efni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to provide empirical evidence of the impact of deferred tax burden, debt contract motivation, and litigation risk on earnings management in the technology and telecommunications sector listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The problem in this study stems from the phenomenon of profit fluctuations, particularly in the technology and telecommunications sectors, which are characterized by high growth but accompanied by competitive pressures and cash flow instability. The methodology used is a quantitative approach with a causal research type. The sample for this study was taken through purposive sampling based on predetermined criteria, resulting in 23 companies with a total of 115 data points. The analysis technique applied is multiple linear regression with the help of SPSS (Statistical Product Service Solutions) software version 25. The F-test results indicate that collectively, deferred tax burden, debt contract motivation, and litigation risk have a significant impact on earnings management with a significance value of 0.000 < 0.05. The T-test results indicate that deferred tax burden has a significant positive impact on earnings management with a sig. 0.014 < 0.05, debt contract motivation has a significant negative impact on earnings management with a sig. 0.000 < 0.05, and litigation risk has a significant positive impact on earnings management with a sig. 0.003 < 0.05. The limitations of this finding are that it is only centered on technology and telecommunication sector companies listed on the IDX, so the results cannot be generalized to other sectors and this finding limits the analysis to only three independent variables, without exploring other factors that may contribute. This finding implies that it can be used as an indicator in evaluating the integrity of a company's financial statements, especially before making investment decisions and further this research can be used for further research in sectors that are more vulnerable to earnings management, especially in the technology and telecommunication sector.